Adipocyte Enhancer-Binding Protein 1 (AEBP1) (a Novel Macrophage Proinflammatory Mediator) Overexpression Promotes and Ablation Attenuates Atherosclerosis in ApoE⁻′⁻ and LDLR⁻′⁻ Mice - Bogachev, Oleg (2011)
Atherogenesis is a long-term process that involves inflammatory response coupled with metabolic dysfunction. Foam cell formation and macrophage inflammatory response are two key events in atherogenesis. Adipocyte enhancer-binding protein 1 (AEBP1) has been shown to impede macrophage cholesterol efflux, promoting foam cell formation, via peroxisome proliferator-activated receptor (PPAR)-γl and liver X receptor α (LXRα) downregulation. Moreover, AEBP1 has been shown to promote macrophage inflammatory responsiveness by inducing nuclear factor (NF)-κB activity via IκBα downregulation. Lipopolysaccharide (LPS)-induced suppression of pivotal macrophage cholesterol efflux mediators, leading to foam cell formation, has been shown to be mediated by AEBP₁. Herein, we showed that AEBP₁-transgenic mice (AEBP1ᵀᴳ) with macrophage-specific AEBP1 overexpression exhibit hyperlipidemia and develop atherosclerotic lesions in their proximal aortas. Consistently, ablation of AEBP₁ results in significant attenuation of atherosclerosis (males: 3.2-fold, P = 0.001 (en face)), 2.7-fold, P = 0.0004 (aortic roots); females: 2.1-fold, P = 0.0026 (en face), 1.7-fold, P = 0.0126 (aortic roots)) in the AEBP₁⁻′⁻/low-density lipoprotein receptor (LDLR)⁻′⁻ double-knockout (KO) mice. Bone marrow (BM) transplantation experiments further revealed that LDLR⁻′⁻ mice reconstituted with AEBP₁⁻′⁻/LDLR⁻′⁻ BM cells (LDLR⁻′⁻/KO-BM chimera) display significant reduction of atherosclerosis lesions (en face: 2.0-fold, P = 0.0268; aortic roots: 1.7-fold, P = 0.05) compared with control mice reconstituted with AEBP₁⁺′⁺/LDLR⁻′⁻ BM cells (LDLR⁻′⁻/WT-BM chimera). Furthermore, transplantation of AEBP1TG BM cells with the normal apolipoprotein E (ApoE) gene into ApoE⁻′⁻ mice (ApoE⁻′⁻/TG-BM chimera) leads to significant development of atherosclerosis (males: 2.5-fold, P = 0.0001 (en face), 4.7-fold, P = 0.0001 [aortic roots]; females: 1.8-fold, P = 0.0001 (en face), 3.0-fold, P = 0.0001 [aortic roots]) despite the restoration of ApoE expression. Macrophages from ApoE⁻′⁻/TG-BM chimeric mice express reduced levels of PPARγ₁, LXRα, ATP-binding cassette A₁ (ABCA₁) and ATP-binding cassette G₁ (ABCG₁) and increased levels of the inflammatory mediators interleukin (IL)-6 and tumor necrosis factor (TNF)-α compared with macrophages of control chimeric mice (ApoE⁻′⁻/NT-BM) that received AEBP₁ nontransgenic (AEBP₁ᴺᵀ) BM cells. Our in vivo experimental data strongly suggest that macrophage AEBP₁ plays critical regulatory roles in atherogenesis, and it may serve as a potential therapeutic target for the prevention or treatment of atherosclerosis.